2016
DOI: 10.1111/nph.14265
|View full text |Cite
|
Sign up to set email alerts
|

Interconnections between meiotic recombination and sequence polymorphism in plant genomes

Abstract: 1022I.1022II.1023III.1023IV.1025V.10261027References1027 Summary Meiosis is fundamental to sexual reproduction and creates genetic variation in progeny. During meiosis paired homologous chromosomes undergo recombination, which can result in reciprocal crossovers. This process can recombine independently arising mutations onto the same chromosome. Recombination locations are highly variable between meioses, although total crossover numbers are tightly regulated. In addition to the effect of meiosis on genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
(161 reference statements)
2
10
1
Order By: Relevance
“…Further, our study of hybrid 3 intervals interactions indicated that the contribution of the cis effects was two times larger than that of trans effects when it comes to explaining the variance of recombination rate. Our results altogether suggest that heterozygosity alone is not sufficient to explain the variation observed in CO numbers and positions across hybrids, in accordance with previous works (Salomé et al 2012;Bauer et al 2013;Rodgers-Melnick et al 2015;Ziolkowski and Henderson 2017). CO control may also depend on other factors such as structural differences between homologous genomes that can inhibit CO formation as observed in A. thaliana (Fransz et al 2016), or modify CO frequency as suggested in maize (Bauer et al 2013;Rodgers-Melnick et al 2015).…”
Section: Genetic Control Of Recombination Ratesupporting
confidence: 89%
“…Further, our study of hybrid 3 intervals interactions indicated that the contribution of the cis effects was two times larger than that of trans effects when it comes to explaining the variance of recombination rate. Our results altogether suggest that heterozygosity alone is not sufficient to explain the variation observed in CO numbers and positions across hybrids, in accordance with previous works (Salomé et al 2012;Bauer et al 2013;Rodgers-Melnick et al 2015;Ziolkowski and Henderson 2017). CO control may also depend on other factors such as structural differences between homologous genomes that can inhibit CO formation as observed in A. thaliana (Fransz et al 2016), or modify CO frequency as suggested in maize (Bauer et al 2013;Rodgers-Melnick et al 2015).…”
Section: Genetic Control Of Recombination Ratesupporting
confidence: 89%
“…This points to the presence of trans acting factors modulating CO formation, in addition to possible cis effects. Our results altogether suggest that heterozygosity alone is not sufficient to explain the variation observed in CO numbers and positions across hybrids, as previously reported [8,5860,60]. CO control may also depend on other factors such as structural differences between homologous genomes that can (1) inhibit CO formation as observed in A. thaliana [61], or (2) modify CO frequency as suggested in maize [8,58].…”
Section: Discussionsupporting
confidence: 67%
“…Following the seminal works of Ross et al ( 1997 ) and Klimyuk and Jones ( 1997 ), great strides have been made in elucidating the basic molecular mechanisms of meiosis and meiotic recombination in plants. As a series of recent reviews have provided comprehensive insights into these processes (Lambing et al 2017 ; Lambing and Heckmann 2018 ; Lawrence et al 2017 ; Mercier et al 2015 ; Mézard et al 2015 ; Ziolkowski and Henderson 2017 ), we will only briefly outline some key aspects here.…”
Section: Control Of Co Formation In Plantsmentioning
confidence: 99%
“…It has long been observed that CO frequencies tend to decrease between regions with increased sequence divergence (Borts and Haber 1987 ; Liharska et al 1996 ; Ziolkowski and Henderson 2017 ). Local inhibition of recombination due to sequence divergence is usually attributed to the presence of mismatched base pairs within recombination intermediates.…”
Section: Control Of Co Formation In Plantsmentioning
confidence: 99%